A new application of the reproducing kernel Hilbert space method to solve MHD Jeffery-Hamel flows problem in nonparallel walls - Inc, Mustafa; Akgul, Ali; Kilicman, Adem (Hindawi Publishing Corporation, 2013)
The present paper emphasizes Jeffery-Hamel flow: fluid flow between two rigid plane walls, where the angle between them is 2 alpha. A new method called the reproducing kernel Hilbert space method (RKHSM) is briefly introduced. The validity of the reproducing kernel method is set by comparing our results with HAM, DTM, and HPM and numerical results for different values of H, alpha, and Re. The results show up that the proposed reproducing kernel method can achieve good results in predicting the solutions of such problems. Comparison between obtained results showed that RKHSM is more acceptable and accurate than other methods. This method is very useful and applicable for solving nonlinear problems.